A basal aïstopod from the earliest Pennsylvanian of Canada, and the antiquity of the first limbless tetrapod lineage - Jason D. Pardo; Arjan Mann (Royal Society Open Science, 2018)
Earliest Pennsylvanian (Bashkirian) vertebrate fossil assemblages of the Joggins Formation (Cumberland Group) of Nova Scotia, Canada, have long been noted for the unique representation of the earliest known crown amniotes, but the overall vertebrate fauna remains poorly understood. The vast majority of Joggins vertebrates have historically been assigned to the Microsauria, a group originally established by Dawson specifically to accommodate the abundant, diminutive fossils of the Joggins Formation. As the Microsauria concept has evolved, some Joggins taxa (e.g. the eureptile Hylonomus lyelli) have been removed from the group, but many of the Joggins ‘microsaurs’ remain unrevised, obscuring the true diversity of the earliest Pennsylvanian tetrapod fauna. Here we amend part of this problem by revisiting the morphology of Dawson's ‘microsaur’ Hylerpeton longidentatum. This taxon, represented by the anterior half of a left hemimandible, is here reinterpreted as a plesiomorphic aïstopod and assigned to a new genus, Andersonerpeton. A. longidentatum shows a surprisingly primitive anatomy of the lower jaw, retaining a parasymphyseal fang pair on the dentary, an adsymphyseal bone bearing a denticle field, fangs on all coronoids and parasymphyseal foramina, as well as a prearticular which extends far anterior along the coronoid series. However, several aïstopod characters can also be seen, including a lack of sculpturing on the dentary and a reduced number of recurved, weakly socketed teeth. The anatomy of A. longidentatum corroborates recent phylogenetic work which has placed the origin of aïstopods within the Devonian fin-to-limb transition but preserves a mosaic of characteristics suggesting an even earlier divergence. The presence of an aïstopod in the Joggins fauna expands the taxonomic diversity of the Joggins fauna and suggests that Joggins may preserve a more typical Carboniferous fauna than previously thought.